Pathophysiology and Complications of Portal Hypertension in Liver Cirrhosis - Rajekar, Harshal (Medical Science: Recent Advances and Applications Vol. 5, 2025)
Portal hypertension is responsible for most of the complications that mark the transition from compensated to decompensated cirrhosis, namely variceal haemorrhage, ascites and hepatic encephalopathy. Portal hypertension also seems to be pathogenetically closely linked to the development of pulmonary complications seen in liver disease: hepatopulmonary syndrome and porto-pulmonary hypertension. Gastroesophageal varices result almost solely from portal hypertension, although the hyperdynamic circulation contributes to variceal growth and rupture. Ascites results from sinusoidal hypertension (portal hypertension) and sodium retention, which is, in turn, secondary to vasodilatation and activation of neurohumoral systems. The predictive value of noninvasive methods such as fibroscan, spleen size, portal vein diameter, and transient elastography in the diagnosis of oesophagal varices remains to be established. Hepatorenal syndrome results from extreme vasodilatation with extreme decrease in effective blood volume and maximal activation of vasoconstrictive systems, renal vasoconstriction, and renal failure, which is probably an indirect effect of the changes in splanchnic circulation. Spontaneous bacterial peritonitis, a frequent precipitant of the hepatorenal syndrome, results from deficient immunity and mucosal defences, resulting in pathological gut bacterial translocation. Hepatic encephalopathy results from portosystemic shunting and hepatic insufficiency, leading to the accumulation of neurotoxins, mainly ammonia, in the brain. The development of portal hypertension and its complications has important prognostic value. Management of portal hypertension needs to be individualised to attain maximum benefit and appropriate utilisation of scarce resources.